Caracterización de los Fisioterapeutas que atienden pacientes Covid-19, en emergencia sanitaria: Characterization of the physiotherapists who care for COVID-19 patients, in a health emergency (La U Investiga, 2020)
The study aims to characterize the physiotherapists who work in the care of COVID-19 patients, analyzing sociodemographic factors, number of daily visits, type of interventions, use of protective clothing and case of contagion in professionals. Seventy subjects, public and private hospital workers, were contacted, who answered a questionnaire with closed questions developed by the authors, with the advice of professional experts in the field of respiratory therapy. The study is descriptive, qualitative-quantitative, cross-sectional. Sociodemographic characteristics, number of patients seen daily, use of protective clothing, testing for COVID19 detection, and percentage of infections were identified. 74.3% of professionals self-identify with thefemale gender, 74.3% do not have a specialty, 91.4 of professionals work in public entities. 32.9% attend an average of 6 to 10 COVID-19 patients daily. Professionals use all recommended physiotherapeutic interventions for the care of COVID-19 patients, as well as use all the necessary protective clothing to avoid contagion. They also point out that COVID-19 detection tests were mostly carried out by control. Of these, aminimal proportion reported contagion.
Keywords: Physiotherapists; COVID-19; health emergency; physiotherapeutic intervention